ГДЗ решебник алгебра 7 класс Звавич

Вариант 2

с-28

 

1. 1) a) p (a + b) = pa + pb;
б) -у(k + c) = -уk - ус;
в) а(k + с - 3) = аk + ас - 3а;
г) -х(а - b + 1) = -ха + xb - x;
2) а) 5а2(2 - а) = 10а2 - 5а3;
6) -8b3(b - 2b2) = -8b4 + 16b5;
в) -7х3(x5 + 3x) = -7х8 - 21х4;
г) (у15 + y20) • 12у23 = 12y38 + 12y43;
3) a) 2m4(m5 - m3 - 1) = 2m9 - 2m7 - 2m4;
б) -3с(с3 + с - 4) = -3с4 - 3с2 + 12с;
в) (8а2 - 4а + 16) • 0,25а = 2а3 - а + 4а;
г) 2х(3х2 + 5ху - у2) = 6х3 + 10x2y - 2ху2;
д) b5(b6 - 5b3 + b - 3) = b11 - 5b8 + b6 - 3b5;
е) -9р(-2р4 + р2 - 2р + 1) = 18p5 - 9p3 + 18р2 - 9р.

2. 1) a) (a + b)p = ap + bp;
6) -k(m - n) = -km + kn;
2) a) a(p - x + y) = ap - ax + ay;
6) (x + у + z) • (-bc) = -bcx - bcy - bcz;
3) a) у22 - ху) = х2у2 - ху3;
б) (х - 1) • ху2 = х2у2 - ху2.

3. 1) а) 5(a + 2) + (а + 2) = 5a + 10 + a + 2 = 6a + 12;
б) (x - 3) - 3(x - 3) = x - 3 - 3x + 9 = -2x + 6;
в) 7(х - 7) - 3(х - 3) = 7х - 49 - 3x + 9 = 4x - 40;
г) 15(8x - 1) - 8(15x + 4) = 120x - 15 - 120x - 32 = -47;
2) a) 2х(х + 1) - 4х(2 - х) = 2х2 + 2х - 8x + 4х2 = 6x2 - 6x;
6) 2у(2х - 3у) - 3у(5у - 3х) = 4ху - 6у2 - 15у2 + 9ху = -21у2 + 13ху;
в) 3c(c + d) + 3d(c - d) = 3с2 + 3cd + 3cd - 3d2 = 3с2 + 6cd - 3d2;
г) 5b(3а - b) - 3а(5b + a) = 15ab - 5b2 - 15ab - 3а2 = -5b2 - 3а2;
3) а) x(x2 + x) - (x2 + x + 1) = x3 + x2 - x2 - х - 1 = х3 - х - 1;
6) 2y2(6y - 1) + 3y(y - 4y2) = 12y3 - 2y2 + 3y2 - 12y3 = y2;
в) а (2а2 - 3n) - n(2n2 + а) = 2а - 3an - 2n3 - аn = 2а - 4an - 2n;
г) b(b3 - b2 + b) - (b3 - b2 + b) = b4 - b3 + b2 - b3 + b2 - b = b4 - 2b3 + 2b2 - b.

4. 1) с(2а - 2с) + а(3с - а) - 2(а - с2) = 2ас - 2с2 + 3ас - а2 - 2а + 2с2 = 5ас - а - 2а;
5 • (-0,1) • 0,7 - (-0,1)2 + 0,2 = -0,16;
2) р22 + 5р - 1) - 3р(р3 + 5р2 - р) + 2р4 + 10р3 - 2р2 =
= р4 + 5р3 - р2 - 3р4 - 15р3 + 3р2 + 2р4 + 10р3 - 2р2 = 0,

в частности, это выражение равно 0 и при р = 3 1/3.

5. 1) а) (а4 - а3b + а2b2 - ab3) • а2b = а6b - а5b2 + а4b3 - а3b4;
б) 2k2x3(3x3 + 2k2 - k - k2) = 6x6k2 + 4х5k2 - 2k3х3 - 2k4х3;
2) а) 5x(3х3 - х2 - ах + а3)а = (15x4 - 5x3 - 5ах2 + 5а3х)а = 15ах4 - 5aх3 - 5а2х2 + 5а4х;
б) -аb(а2b - аb2 - а3b3) • р = -а3b2р + а2b3р + а4b4р.